2015
DOI: 10.4238/2015.january.30.13
|View full text |Cite
|
Sign up to set email alerts
|

Association between ERCC1 and XPF polymorphisms and risk of colorectal cancer

Abstract: ABSTRACT. We conducted a hospital-based case-control study to evaluate the association between polymorphisms in excision repair cross-complementing group 1-xeroderma pigmentosum group F (ERCC1-XPF) variants and the risk of colorectal cancer in a Chinese population. Genotyping of the ERCC1 rs2298881 and rs11615 and XPF rs2276466 polymorphisms were detected by polymerase chain reactionrestriction fragment length polymorphism. Colorectal cancer cases were more likely to be smokers, consume alcohol, have higher en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
6
14
0
Order By: Relevance
“…For instance, some Chinese [27,32] and Norwegian [33] studies assessed the ERCC1-rs11615 polymorphism and CRC risk but found no significant correlations [34], in accordance with the findings of the present study. In contrast, another Asian study showed that the ERCC1-rs11615 genotype T/T contributed to an increased CRC risk compared to CC genotype, although the risk was only marginal [35].…”
Section: Polymorphisms and Cancer Risksupporting
confidence: 91%
See 1 more Smart Citation
“…For instance, some Chinese [27,32] and Norwegian [33] studies assessed the ERCC1-rs11615 polymorphism and CRC risk but found no significant correlations [34], in accordance with the findings of the present study. In contrast, another Asian study showed that the ERCC1-rs11615 genotype T/T contributed to an increased CRC risk compared to CC genotype, although the risk was only marginal [35].…”
Section: Polymorphisms and Cancer Risksupporting
confidence: 91%
“…As an example, the XRCC1-rs25487 A allele ranges from 0.11 in the African population to 0.37 in European population [25], hence possibly contributing to different levels of susceptibility to CRC across populations. While previous studies on XRCC1-rs25487 confirmed the association of increased risk for CRC in particular among East Asians and Arab ethnicity [26][27][28][29], two meta-analysis studies, consistent with our results, suggested no association of this SNP and risk of CRC [30,31]. Further large and well characterized studies, therefore, are needed to identify the association between the XRCC1-rs25487 polymorphism and CRC risk and how it varies in different populations.…”
Section: Polymorphisms and Cancer Risksupporting
confidence: 84%
“…Some Chinese [24,29] and Norwegian [30] studies assessed the ERCC1-rs11615 polymorphism and CRC risk but found no significant correlations [31], in accordance with the findings of the present study. In contrast, a study of a Chinese population showed that the ERCC1-rs11615 genotype T/T contributed to a 1.9-fold increased CRC risk compared to CC genotype [32].…”
Section: Polymorphisms and Cancer Risksupporting
confidence: 91%
“…As an example, the XRCC1-rs25487 A allele ranges from 0.11 in the African population to 0.37 in European population [22], hence possibly contributing to different levels of susceptibility to CRC across populations. While previous studies on XRCC1-rs25487 confirmed the association of increased risk for CRC in particular among East Asians and Arab ethnicity [23][24][25][26], two meta-analysis studies, consistent with our results, suggested no association of this SNP and risk of CRC [27,28]. Further large and well characterized studies, therefore, are needed to identify the association between the XRCC1-rs25487 polymorphism and CRC risk and how it varies in different populations.…”
Section: Polymorphisms and Cancer Risksupporting
confidence: 84%
“…Recently, ERCC1 polymorphisms were found to be associated with colorectal cancer risk (Yang et al, 2015). In addition, expression of ERCC1 could predict the clinical outcomes of non-small cell lung cancer patients receiving platinum-based chemotherapy (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%